Sensitization effect between Ln3+ ions in zinc fluoride glasses for MIR applications. Issue 8 (1st June 2019) - Zhou, Lingfeng; Huang, Feifei; Dou, Benle; Li, Yinyan; Ye, Renguang; Wang, Huanping; Xu, Shiqing
Abstract: A system of zinc fluoride glasses were synthesized to analyse the sensitization mechanism between doped Ln 3+ ions under 808 or 980 nm excitation. Differential scanning calorimetry (DSC) curve and Raman spectra indicate the favourable thermal stability and a low maximum phonon energy of the host. Judd-Ofelt (J-O) theory together with the absorption spectra were utilized to compute the Ωt for predicting radiative features of each sample which coincide with the later measured emission spectra. Broadband emission ranging from 2400 to 3300 nm with a half-width of 361 nm in Er 3+ /Dy 3+ codoped zinc fluoride glasses under 980 nm pumping has been investigated, which may be applicated in mid-infrared fiber amplifier and broadband tunable lasers field. On the other hand, the efficient sensitization effect mechanism between Er 3+ and Dy 3+ around 3 μm band with an extremely high energy transfer efficiency Ƞ (96.1%) of Er 3+ : 4 I13/2 →Dy: 6 H11/2 has been researched under 808 nm excitation. Hence, Er 3+ and Dy 3+ doped zinc fluoride glasses may be potential optical candidates of great development foreground in the fields of mid-infrared applications.